Models of Emotional Intelligence : A Review - Kanesan, Pavitra; Norsiah, Binti Fauzan (UKM Publisher, 2019)
This paper review rhe conceptualization of three models of emotional intelligence, goodness and weakness of each models such as ability model, mixed model and trait model